Defining advantage and athletic performance: The case of Oscar Pistorius - Jones, C.; Wilson, C. (European Journal of Sport Science, 2009)
Olympic style games were first held for athletes with disabilities in Rome in 1960. Today the Paralympic Games (parallel Olympics) feature competition for athletes from six disability groups, including amputee, visually impaired, and spinal cord injury. Olympic hosts, both summer and winter, are now contractually obliged to organize the Paralympics in the same venue. The size and popularity of the games have grown exponentially since their inception, but they remain largely separate from the Olympics themselves. Recently, a very successful Paralympic athlete from South Africa, Oscar Pistorius, made it clear that despite his double below-the-knee amputation he wanted to compete in his event (400 m) at the Olympics. Initially, however, Oscar Pistorius was prohibited from competing at any International Amateur Athletics Federation (IAAF) competition on grounds of fairness. On the basis of biomechanical and physiological evidence, the IAAF argued that his highly specialized prosthetic limbs gave him an advantage and were therefore in contravention of Rule 144.2. This rule forbids the use of any technical device (such as prosthetic limbs) that provides the user with an advantage over another athlete not using such a device. This decision was subsequently overturned by the Court of Arbitration for Sport following an appeal by Pistorius. Using this case as an example, the aim of this paper is to highlight the empirical and ethical difficulties associated with the application of the principle of fairness in sport. In particular, we discuss both the complexity of identifying the nature and size of athletic advantage and the basis for determining its validity. Moreover, we explore how similar difficulties arise when attempting to establish criteria for "relevant athletic performance". We argue that reasonable rules and norms for competition are not simply inferred from the principle of fairness. Such rules and norms should result from careful judgements informed by scientific, conceptual, and ethical evidence, and be guided by the standards of excellence that best characterize the sport in question.